Influence of stereoelectronic interactions on the 13C NMR chemical shift in iodine-containing molecules - Renan V. Viesser; Cláudio F. Tormena (Journal of Magnetic Resonance Open, 2022)
Methyl substitution in ortho position causes a deshielding of 6–7 ppm on the 13C NMR chemical shift of the own methyl group and the carbon nucleus bonded to iodine atom (ipso) in iodobenzene-like molecules. In contrast, the carbon ipso is 3–4 ppm shielded when methyl is in para. To understand how the position of methyl substitution perturbs nuclear magnetic responses in iodobenzene and diacetoxyiodobenzene derivatives, shielding mechanisms are theoretically investigated via density functional theory calculations. We show the relative ortho position between iodine and methyl allows through-space and through-bond interactions to take place, generating additional paramagnetic currents and affecting the spin-orbit coupling propagation. Relevant paramagnetic couplings that explain the para methyl substitution behavior are also presented. Shielding mechanisms discussed here for monomethylated compounds can be summed to predict the 13C NMR chemical shift in multi methyl substituted iodine-containing compounds.